Data analysis of nucleotide sequences in mtdna control regions and development of mutation comparative applications in ethnic papuan (Funded work) - JOHNSON SIALLAGAN; ROSYE H.R. TANJUNG; YOHANIS NGILI (International Journal of Pharma and Bio Sciences, 2019)
The area of ​​the gene controller shows polymorphism in the mtDNA genome. The specific aim of this study is to determine whether the nucleotide sequence of the control regions originating from several individuals has a pattern of mutations in certain patterns of inter-ethnicity. The mtDNA template of each sample is obtained through cell lysis. The template was then amplified by the Polymerase Chain Reaction (PCR) method, observed by agarose gel electrophoresis, and continued with the determination of nucleotide sequences and analysis of the results. Analysis of nucleotide sequences by comparing the revised-Cambridge Reference Sequence (CRS) to determine whether there are mutations that occur in the area of ​​gene control in mtDNA from various tissues of the human body. In this study we will focus on the analysis of the area of ​​the gene controller that will be analyzed about the sequence, and mutation, and the comparison in several other individuals in GenBank for later developed open source application. The mutations to be analyzed are transitional and transverse, deletion and insertion mutations. From the results of this study it was stated that mitochondrial DNA patterns for each hyper variable D-loop region sequence profile in each ethnic group in Papua indicate a specific mutation, so that a certain algorithm can be made that can lead to markers in the blood polymorphic mtDNA. The dominant mutations in the Papuan population are as follows: the dominant mutations in the HVSI region are T16.189c, and C16.223t; while the dominant mutation in the HVSII area is T152c, and A263g. These mutations are divided into substitution mutations: both transitional and transversional. Application development has been carried out for the determination of sequences and mutations in human mitochondrial genome gene control regions.